PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS MEDIA DIORAMA TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM PELAJARAN IPAS KELAS IV MADRASAH IBTIDAIYAH - Indah Herawati, Isti; Nurhaningtyas Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low critical thinking skills of fourth-grade students in IPAS learning, particulary on the topic of seasons and climate in Indonesia, which was caused by the dominance of conventional teaching methods and limited use of concrete learning media. This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by diorama media on student’s critical thinking skills in IPAS learning. The research employed a quantitative approach using a quasi-experimental group methode with a non-equivalent control group design. The population consisted of all fourth-grade students of MI Matholibul Huda Jenggolo Tuban in the 2025/2026. Academic year, totaling 47 students, with class IV A as the experimental group and class IV B as the control group. Data were collected through essay tests administered as pretest and posttests and analyzed using descriptive statictics and inferential statistical tests. The results showed that the average posttest score of the experimental group was higher than that of the control group. The paired sample t-test indicated a significant difference between pretest and posttest scores in both groups, while the independent sample t-test revealed a significant difference between the critical thinking skills of students in the experimental and control groups. These findings indicate that the Problem Based Learning (PBL) model assisted by diorama media has a significant positive effect on improving student’s critical thinking skills in IPAS learning.